THE EXTENT TO WHICH DOWNSTREAM BUYERS ARE ABLE TO FULFIL FLOWER FARMERS NEEDS IN DALAT - Lê, Như Bích (Trường Đại học Đà Lạt, 2023)
This study seeks to examine the gap between what farmers want and what they actually receive from their downstream buyers in Dalat – Vietnam. The sample consisted of 206 chrysanthemum and rose farmers in Dalat and reports on their exchange transactions with their most preferred and second most preferred buyer. Both social and economic criteria are identified as influencing the farmers’ choice of downstream buyer, reinforcing the importance of relational marketing in the transitional economies as a means of risk mitigation.